Lindenmeier redux: spatial patterns of the Lindenmeier Folsom Site (5LR13) - Chambers, Jason Christopher, author; LaBelle, Jason, advisor; Reich, Robin, committee member; Zeidler, James, committee member (Colorado State University. Libraries, 2015)
The Lindenmeier Folsom Site (5LR13) was excavated from 1934-1940 by Frank H. H. Roberts, Jr. of the Smithsonian Institution. Over the course of six field seasons spent excavating the site, the spatial locations of approximately 6,000 items were mapped and recorded by Roberts, and later published as a series of maps in the appendices in the Concluding Report (Wilmsen and Roberts 1978). This thesis has digitally reproduced these maps using ArcGIS mapping software, preserving the spatial relationships between the artifacts mapped during the 1930's excavations, and applying sophisticated spatial analyses to the Lindenmeier dataset to detect spatial patterning. Among other conclusions, this thesis finds that the spatial patterns exhibited at Lindenmeier vary across the site, reflecting different discard patterns enacted by the Folsom camp site occupants. Regarding hideworking and projectile manufacturing activities, the spatial patterns at Lindenmeier do not reflect the patterning at Stewart's Cattle Guard which Jodry (1999) argues as evidence for gendered segregation of space. The spatial patterns at Lindenmeier suggest an integrated suite of activities undertaken across the site with logical segmentation of space and association of tools into specific toolkits. Examining spatial patterns within the distribution of discarded materials at the Lindenmeier Folsom site will contribute greatly to enhancing archaeologists' interpretations of Paleoindian, and specifically Folsom, lifeways on the Great Plains during the Late Pleistocene.
Zip file contains supplementary tables.
Keywords: GIS; Paleoindian; spatial statistics; Lindenmeier; Folsom; Pleistocene